Pengaruh Pemutihan Berkala dan Literasi Wajib Pajak terhadap Kepatuhan PKB Orang Pribadi di Kota Semarang - Shofi Nila Munana; Sri Wahyuning; Iwan Koerniawan; Bambang Widjanarko Susilo; Eni Endaryati (Universitas Sains dan Teknologi Komputer, 2026)
Motor Vehicle Tax (MVT) is one of the main sources of Regional Original Revenue and plays an important role in supporting regional development and providing public services. However, the high level of Motor Vehicle Tax arrears in Semarang City indicates that individual taxpayers' compliance remains suboptimal. This study aims to analyze the effect of Periodic Tax Amnesty and Taxpayer Literacy on Motor Vehicle Tax compliance among individual taxpayers in Semarang City. The study employed a quantitative approach using a causal associative method. Data were collected through questionnaires distributed to 100 individual taxpayers selected via purposive sampling. The data were analyzed using multiple linear regression in SPSS version 25. The results indicate that Periodic Tax Amnesty and Taxpayer Literacy have a significant effect on Motor Vehicle Tax compliance, both partially and simultaneously. The coefficient of determination (R²) of 0.642 indicates that both variables explain 64.2% of the variation in Motor Vehicle Tax compliance, with the remaining 35.8% attributable to other factors outside the research model. The novelty of this study lies in examining the simultaneous effect of Periodic Tax Amnesty and Taxpayer Literacy on Motor Vehicle Tax compliance among individual taxpayers in Semarang City. The findings recommend strengthening taxpayer education programs and implementing periodic tax amnesty policies more targeted to improve taxpayer compliance sustainably.